REVIEW OF MAQĀṢID AL-SHARĪ'AH ON THE PERFORMANCE AND PROFESSIONALISM OF PRODUCTIVE WAQF NADZIR IN INDONESIA - Akhmad Rudi Maswanto; Firma Yudha (JURNAL HAKAM, 2025)
Waqf is one of the instruments of Islamic philanthropy that has great potential in improving the welfare of the people. Nadzir holds a central role as the party responsible for the management and development of waqf assets. This article aims to examine the professionalism and ethics of waqf nadzir from the perspective of Islamic law, using the theory and analysis of maqāṣid al-sharī'ah on the practice of productive waqf in Indonesia. This research uses a qualitative-descriptive approach through the method of literature study, referring to classical and contemporary Islamic law sources as well as national waqf regulations. The results of the study show that efforts to improve the professionalism of a waqf nadzir are to prioritize the principles of Islamic law. Commitment to justice and transparency is a moral-legal responsibility in the management of waqf property. Therefore, strengthening the capacity and integrity of a nadzir is essential to make waqf an instrument for sustainable economic development of the ummah.